Hospitalizações por condições sensíveis à atenção primária em crianças menores de cinco anos, Paraná, 2000 a 2011 - Prezotto, Kelly Holanda (2013)
Hospitalizations for sensitive conditions in primary care are avoidable cases through the activity of primary attention to health. They are highlighted in infant health due to the fact that this section of the population is the target of public health policies in Brazil, especially within the attention milieu. Current investigation, dealing with temporal series of an ecological type, analyzed hospitalization for sensitive conditions in primary care in under-five-year-old children, in the state of Paraná, Brazil, between 2000 and 2011. All hospitalizations of children under five and residing in the state of Paraná were analyzed. Data were retrieved from the Hospital Information System (SIH-SUS) and from the Brazilian Geographic and Statistical Institute (IBGE). Selection of main diagnosis for hospitalization consisted of items in the List of Sensitive Conditions for Primary Care. Profile identification was undertaken by frequency distribution according to age and hospitalization diagnosis and by hospitalization rates for sensitive conditions per 10,000 inhabitants according to the Health Macroregion and the Regional Health District. Trend analysis was done according to hospitalization rates according to age and hospitalization diagnosis followed by the construction of polynomial regression models. The 2000-2011 period was divided into three-year periods, whereas children´s age was subdivided into under-one-year children; 1 to 2-year old children; 3 to 4-year old children. Further, 813,230 hospitalizations of under-five children were reported, featuring 10.2% of cases occurring in sensitive conditions to primary care, although 1-2-year-old children were the main subjects hospitalized in sensitive conditions. The most frequent sensitive cases comprised bacterial pneumonias (40.2%), infectious gastroenteritis (35.8%) and asthma (9.3%). Rate in hospitalizations for sensitive conditions increased when compared to other causes within the eleven Regional Health Districts in the state of Paraná. Results showed a rising trend in hospitalizations sensitive to primary care of under-one-year children and stable conditions in the hospitalization of 3-4-year-old children. A significant increase (p<0.05) occurred in hospitalizations for bacterial pneumonia in children less than one years and for gastrentrites in children less than one year old and in children aged 3 and 4 years. Stability in hospitalization for gastroenteritis occurred in children aged one to two years. The above foregrounds the importance of establishing strong actions for the prevention and early treatment in basic health care. Hospitalization studies on sensitive conditions in primary care demonstrated the main causes that require health team attention for the infant population residing in the state of Paraná. In the case of certain avoidable causes, the probably decrease in hospitalization did not occur throughout the period under analysis as expected. The planning and establishment of effective activities for children under five in the community are mandatory. Nurses become a basic professional in the health team in primary care and in the construction of intensive vigilance to children´s health through team upgrading within the active search for risk factors, mainly in the cases of pneumonia and gastroenteritis, and in quality child care for under-five-year-old children.